TINDAK TUTUR DIREKTIF GURU DALAM WACANA INTERAKSI KELAS ANAK TUNARUNGU - Ardianto Ardianto (Faculty of Languages and Arts, Universitas Negeri Yogyakarta, 2013)
This study aims to describe forms, functions, and strategies of the teacher’s directive speech acts in the discourse of deaf children’s classroom interaction. It employed the qualitative approach. The data were naturalistic in nature, collected from communication occurring in classroom interaction. The findings are as follows. First, the forms include declarative, interrogative, and imperative ones. Second, the functions comprise commands, requests, prohibitions, permissions, suggestions, expectations, invitations, warnings, and elicitations. Third, the strategies consist of direct and indirect ones. The realization of the forms, functions, and strategies of the teacher’s directive speech acts is based on a variety of contexts underlying classroom conversation discourse.